Rheological Evaluation of Modified Bitumen by EVA and Crumb Rubber Using RSM Optimization - Mohamad H. Dehnad; Behrouz Damyar; Hossein Z. Farahani (Advances in Materials Science and Engineering)
In the present study, ethylene-vinyl acetate (EVA) and crumb rubber (CR) were used as bitumen modifiers. The experiment was designed by response surface methodology (RSM) at different levels of modifier additives based on the central composite design (CCD). Next, the Superpave protocol was followed to evaluate the modified bitumen performance at different temperatures compared with the unmodified bitumen. In this regard, to evaluate at high temperatures, a dynamic shear rheometer (DSR) test was performed, and G∗/sinδ index was examined on bitumen samples after aging. Besides, the bending beam rheometer (BBR) test was performed to evaluate the low-temperature behaviour of the modified bitumen according to the SHRP standard based on the creep stiffness and creep rate. The optimal combination of additives was evaluated using RSM and analysis of statistical values to improve the performance properties of bitumen at high and low temperatures. Moreover, based on the DSR and BBR test results, 5.6% of EVA and 3.9% of CR were selected as the optimal values for the modified bitumen behaviour at the high and low temperatures of the mixture.